IgA Vasculitis Following ChAdOx1 nCoV-19 Vaccination - Manabendra Basu; P M Prathibha; B V Murali Mohan (Wolters Kluwer Medknow Publications, 2024)
IgA vasculitis (IgAV), a small-vessel vasculitis, is more frequently seen in children than in adults. IgAV is triggered by various bacterial and viral infective agents. Here, we are describing a case of IgAV following ChAdOx1 nCoV-19 vaccination. A 39-year-old male presented with skin rash, joint pain, and pain abdomen. Symptoms started within 3 days of ChAdOx1 nCoV-19 vaccination. His clinical examination and investigations lead to a diagnosis of IgAV. After ruling out other possible etiologies, we concluded it as vaccine-induced IgAV. A few cases of IgAV have been reported worldwide post SARS-CoV-2 vaccination. Although rare and often self-limited, it is important to recognize the possibility of IgAV post-SARS-CoV-2 vaccination because early recognition, initiation of treatment, and timely follow-up can improve the disease outcome.